(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
A new morphological group of advanced Siphonodella with diagonal or/and longitudinal ribbed ornamentation on the upper side of the platform of the P1 elements was identified and described based on the author’s paleontological material from the Polar Urals and published data from East European, Central, and Northeast Asian successions. The group includes two valid species Siphonodella nandongensis Li and Siphonodella vladimirovi Plotitsyn nom. nov. Due to the low representativeness of the paleontological material, eight taxa are described in an open nomenclature under the species names Siphonodella sp. A-H. Siphonodella vladimirovi is described as a nomen novum in accordance with the recommendations of the International code of zoological nomenclature (previously identified species appeared under the invalid species names Siphonodella diagonalica Pazukhin or Siphonodella zeravshanica Bardasheva). It is assumed that the species Siphonodella nandongensis Li, Siphonodella vladimirovi Plotitsyn, and Siphonodella sp. A-H came from morphologically similar species from the cosmopolitan group or as descendants of the East European group.